2007
DOI: 10.1111/j.1600-0714.2007.00530.x
|View full text |Cite
|
Sign up to set email alerts
|

Coexistence of Sjögren's syndrome and sarcoidosis: a report of five cases

Abstract: Our findings appear to support a true coexistence of sarcoidosis with SS. Therefore, it is reasonable to suggest removing the exclusion of sarcoidosis from the diagnostic criteria for SS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 23 publications
0
23
0
1
Order By: Relevance
“…to our knowledge, reports of a coexistence of both conditions with histological proof of sarcoidosis are relatively scarce [4][5][6][7]. Our case underlines how important pathology can be to establish the true coincidence of sarcoidosis with pSS.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…to our knowledge, reports of a coexistence of both conditions with histological proof of sarcoidosis are relatively scarce [4][5][6][7]. Our case underlines how important pathology can be to establish the true coincidence of sarcoidosis with pSS.…”
Section: Discussionmentioning
confidence: 73%
“…If such classification criteria were taken as "the truth" in clinical practice, sarcoidosis and pSS would be regarded as mutually exclusive conditions and their coexistence regulated as "impossible" or at least "unlawful." however, the prevalence of sarcoidosis in large series of patients with pSS ranges from 1 to 2 % [4][5][6]. although classification criteria are not to be taken as diagnostic criteria, they are bound to affect clinicians' decisions and perceptions in clinical practice and induce diagnostic error or suboptimal management.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They reported that they demonstrated sarcoidosis and Sjögren's association but noted sarcoidosis should not be present as an exclusion criterion in diagnosing SS. Mansour et al (2) and defined their accounting for the diagnosis criteria of both diseases as an association in their series of five cases and they made the SS diagnosis by using American-European criteria (at least one auto-antibody or accounting for four criteria out of six accompanying biopsy). They also pathologically demonstrated sarcoidosis diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Luis et al presented two cases of sarcoidosis with lung involvement and Sjogren's Syndrome. In that cases, noncaseating granuloma and lymphocytic interstitial pneumonitis were identified in the lung pathology (23)(24)(25). Combined pulmonary sarcoidosis and lung involvement of Siogren's Syndrome may require lung biopsy to show noncaseating g r a n u l o m a s a n d lymphocityc interstitial pneumonitis.…”
Section: Sarcoidosis and Sjogren's Syndromementioning
confidence: 99%